Impact of Inflation on Living Standard of People: An Econometrics Analysis of Sri Lanka - Francis, S.J.; Afriha, F.A.M. (Journal of Business Economics and Management Studies, 2024)
The continuous increase in the general price level of goods and services in an economy is known as inflation. The domestic value of money continuous to decline as the general price level rises, and reducing the purchasing power of the people. Therefore, it is important to know the exact relationship between living standard of people and inflation. Hence the main objective of this study was to examine the impact of inflation on living standard of people in the context of Sri Lanka over the period of 1990-2022. The Human Development Index has been used to measure the living standard of people in this study. The data of Human Development Index, Consumption Expenditure, Government Expenditure on Social Welfare and Labour Force Participation Rate were collected from annual reports of Central Bank of Sri Lanka. The ADF and PP unit root tests confirmed that none of the variables are I (2), which allow to examine co-integrating relationship among the variable using ARDL Bound testing method. The ARDL Bound testing result conformed that, there is a co-integrating relationship between the variables. Further this test suggests that, inflation has negative and significant impact on living standard of People in the long run. Moreover, the Error Correction Model found that, inflation has positive and significant impact on living standard of People in the short run. Also, granger Causality Test reveals that uni-directional causality runs from inflation to living standard of people. Finally, the results of this study show that, inflation negatively effects on living standard of People in the long run. At the same time there is a uni-direcrional causation between these two variables. This conclusion emphasizes that, in order to improve the living standard of People inflation could be used as a policy instrument in the long run.
Keywords: Living Standard; Inflation; ARDL Bound test